Development Of Spiritual Value-Based Apparatus Resources - Fitriyah, Nina Sa'idah Fitriyah; Muh Hamdi Zain; Nabila Makki; Nia Agus Saputri (POLITICO, 2024)
This study aims to analyze the Development of the State Civil Apparatus (ASN) from the perspective of spiritual values. ASN development is a strategic component in improving government effectiveness and the quality of public services. Traditional technical-based methods are no longer sufficient to meet the needs of human resource management in the difficult contemporary era. This study looks at the ASN development model from the perspective of spiritual values. This model combines elements of ethics, spirituality, and professionalism in the formation of ASN's character and performance. The implementation of spiritual values in the development of ASN in Situbondo Regency using a qualitative descriptive approach. This method uses ordinary religious activities, such as the recitation of prayers and Khataman Al-Qur'an, as a means to build character and work ethics. The results of the study show that incorporating spiritual values into the ASN development program is very helpful in the formation of ASN who not only have technical skills but also honest and caring people. In addition, this research reveals that spiritual-based leadership plays an important role in encouraging ASN involvement, creating a harmonious work environment, and increasing productivity. The development of spirituality-based ASN also supports the achievement of transparent, accountable, and effective governance. Thus, spiritual values can be a strategic foundation to realize professional and character civil servant as well as support the sustainable transformation of public services.